Prospectus 2005/2006 : A World-Class University / Corporate Communications & International Relations Office, UiTM - Corporate Communications & International Relations Office, UiTM (Corporate Communications & International Relations Office, UiTM, 2005)
This detailed and comprehensive Prospectus is our way of making the university accessible to you. This will give you an insight into the diverse academic programmes available and their management, as well as the community of people involved in making UiTM as institution of higher learning that is highly recognized nationally and internationally.